Assessment of Noise Levels of Equipment Used in the Practical Dental Teaching Activities. (1st March 2021) - Amine, Meriem; Aljalil, Zineb; Redwane, Asmaa; Delfag, Ikram; Lahby, Imane; Bennani, Anas
Abstract : Introduction . Practical activities in dentistry are characterized by a high noise level that can have adverse effects on the hearing health of professors, students, and teaching staff. The objective of our study was to make an assessment of the noise level during the practical fixed prosthodontics activities in the Faculty of Dentistry of Casablanca. Materials and Methods . We conducted a descriptive cross-sectional study to measure the noise level in the practical room of fixed prosthodontics. The measurements were obtained during 4 sessions over a duration of 2 hours and 30 minutes, each with the use of a SdB + sound level meter at 4 different locations. Results . The results showed the following: an average value of 69.35 dB ( A ) for the first practical session (south), an average value of 71.07 dB ( A ) for the 2nd practical session (east), an average value of 70.36 dB ( A ) for the 3rd practical session (west), and an average value of 72.06 dB ( A ) for the 4th practical session (center of the room). Discussion and Conclusion . The results obtained are similar to the results found in previous studies in other countries. These results are below the thresholds of the legislation and international standards. However, we have recorded punctual peaks that exceed the recommended level, requiring the introduction of the means of prevention and the measures of safety against the noise as well at the level of the practical activity classroom and the realization of more in-depth studies concerning the evaluation of the daily exposure of the professors, students, and teaching staff to noise.